Chemical Biology Interrogates Protein Arginine Phosphorylation. Issue 8 (18th August 2016) - Suskiewicz, Marcin Józef; Clausen, Tim
Abstract : Protein arginine phosphorylation has emerged as an important regulatory mechanism in Gram-positive bacteria, yet a couple of key mysteries remain. In this issue of Cell Chemical Biology, Fuhrmann et al. (2016) use activity-based probes to demonstrate that the protein arginine phosphatase YwlE is inactivated upon oxidative stress to unleash heat-shock gene expression. Abstract : Protein arginine phosphorylation has emerged as an important regulatory mechanism in Gram-positive bacteria, yet a couple of key mysteries remain. In this issue of Cell Chemical Biology, Fuhrmann et al. (2016) use activity-based probes to demonstrate that the protein arginine phosphatase YwlE is inactivated upon oxidative stress to unleash heat-shock gene expression.